2017
DOI: 10.1002/ejoc.201700725
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Resorcinarene Cavitands in Metal‐Based Catalysis

Abstract: Catalytic chemistry involving coordination complexes based on resorcinarene cavitands has been little explored in comparison to the many studies concerning the use of such ligands in classical coordination chemistry or host–guest chemistry. The potential utility of resorcinarene cavitands in catalysis arises essentially from two features: (1) their ability to function as ligands suitable for metal confinement and thus to make reactions either shape selective or to enhance their rates through supramolecular ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 98 publications
0
22
0
Order By: Relevance
“… 16 , 17 The so-called bowl complexes, presenting three imidazole arms on their large rim, 18 were shown, when complexing a zinc cation, to present two labile sites in the cis position relative to each other, which opened new opportunities for recognition and reactivity. 19 23 …”
Section: Introductionmentioning
confidence: 99%
“… 16 , 17 The so-called bowl complexes, presenting three imidazole arms on their large rim, 18 were shown, when complexing a zinc cation, to present two labile sites in the cis position relative to each other, which opened new opportunities for recognition and reactivity. 19 23 …”
Section: Introductionmentioning
confidence: 99%
“…Matt's research currently focuses on metal confinement and molecular transition‐metal catalysts based on cavity‐shaped molecules, notably calixarenes, resorcinarenes, and cyclodextrins. He has reported in Chemistry—A European Journal on metal confinement through N‐heterocyclic carbenes, and in the European Journal of Organic Chemistry on resorcinarene cavitands in metal‐based catalysis …”
Section: Awarded …mentioning
confidence: 99%
“…as multi-and mono-dentate bowlshaped ligands in several transition metal catalysed crosscoupling reactions. [6,7] Furthermore, tri-dentate resorcinarene ligands with imidazole binding sites were used as biomimetic model-compounds to study various zinc and copper based enzymatic binding sites, reported by Reinaud et al [8][9][10] Molecular resorcinarene-based capsules connected by three linkers have been reported, [11,12] some of them even with a photosensitive gate, [13] as well as dimers with only one covalent bond between the resorcinarene-units. [14,15] All these examples derive from tri-or mono-functionalized resorcinarenes.…”
Section: Introductionmentioning
confidence: 99%